2018
DOI: 10.1002/mrm.27502
|View full text |Cite
|
Sign up to set email alerts
|

Rapid T1 quantification from high resolution 3D data with model‐based reconstruction

Abstract: Purpose Magnetic resonance imaging protocols for the assessment of quantitative information suffer from long acquisition times since multiple measurements in a parametric dimension are required. To facilitate the clinical applicability, accelerating the acquisition is of high importance. To this end, we propose a model‐based optimization framework in conjunction with undersampling 3D radial stack‐of‐stars data. Theory and Methods High resolution 3D T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
81
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(98 citation statements)
references
References 46 publications
(117 reference statements)
2
81
0
Order By: Relevance
“…This case can be computed again by a proximal method,such as the nested primaldual algorithm 27 described in Section 2.4.2. Let us note that in the case of a nonconvex d, as in our case, the proximal Newton method converges to the closest minimum, 44,45 if the minimization steps are not too large.…”
Section: Proximal Newton Methodsmentioning
confidence: 87%
“…This case can be computed again by a proximal method,such as the nested primaldual algorithm 27 described in Section 2.4.2. Let us note that in the case of a nonconvex d, as in our case, the proximal Newton method converges to the closest minimum, 44,45 if the minimization steps are not too large.…”
Section: Proximal Newton Methodsmentioning
confidence: 87%
“…In order to get better time of computational we decided to choose a simple and efficient method of model fitting. Other solutions, in some cases are more efficient but are also numerically advanced, and require more time to reconstruct the final image [16][17][18][19][27][28][29]33]. In the literature we did not find any benchmark that enables us to compare methods of T 1 mapping reconstruction and quality of results of different works for similar data.…”
Section: Time Complexitymentioning
confidence: 99%
“…Acceleration using GPU and implementation of some methods in C/CUDA (Compute Unified Device Architecture) generates a time complexity of 10-20 min [19,33] and in the range from minutes to hours depending on data size [18]. Fast multi-slice method for T 2 mapping [29] calculates 50 slices on an office computer within 7 h, which gives approximately 9 min per slice or alternatively rapid T 1 quantification [28] reports reconstruction time of approximately 10 min per slice. We showed that a single iteration of the FIR-MAP for all projections could take 30 s. The data preparation of initial model for all projections took an additional 2 min for IFM and 1 min for MFM.…”
Section: Time Complexitymentioning
confidence: 99%
See 2 more Smart Citations